AUC‐Guided Vancomycin Dosing in Adolescent Patients With Suspected Sepsis. (15th July 2016) - Lanke, Shankar; Yu, Tian; Rower, Joseph E.; Balch, Alfred H.; Korgenski, E. Kent; Sherwin, Catherine M.
Abstract: Vancomycin is a first‐line treatment for β‐lactam‐resistant Gram‐positive bacterial infections. Understanding the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of vancomycin in an adolescent population is of clinical importance in this often overlooked pediatric population. This retrospective study investigated vancomycin PK‐PD in an adolescent cohort (12 to 18 years of age) of 463 patients (57% male, 81% white) admitted to the Intermountain Healthcare System between January 2006 and December 2013. Population PK modeling was performed in NONMEM 7.3. Vancomycin PK was well described with a 1‐compartment model that identified both body weight (WT) and creatinine clearance (CRCL) as covariates significantly impacting vancomycin disposition. The model was then utilized to determine dosing strategies that achieved the targeted area under the 24‐hour time curve vs minimum inhibitory concentration (AUC0‐24 /MIC) ratio of ≥400. Additionally, these data were correlated with minimum steady‐state concentrations (Css, min ) to find an acceptable target trough concentration range in adolescents. This analysis demonstrated that Css, min ranging from 10 to 12.5 mg/L were highly predictive of achieving an AUC0‐24 /MIC ≥400 when the MIC was ≤1 mg/L. These results suggest that the target trough concentration for adolescents may be lower than that for adults.